Books and islands in Ojibwe country : traveling through the land of my ancestors - Erdrich, Louise (New York : Harper Perennial, 2014)
"An account of Louise Erdrich's trip through the lakes and islands of southern Ontario with her 18-month old baby and the baby's father, an Ojibwe spiritual leader and guide"--
Books and Islands -- Islands -- Rock Paintings -- Books -- Home -- Afterword.
"A hardcover edition of this book was published in 2003 by the National Geographic Society"--Title page verso.
Keywords: Erdrich, Louise -- Travel -- Lake of the Woods Region; Erdrich, Louise -- Family; Ojibwa Indians -- Lake of the Woods Region; Islands -- Lake of the Woods Region; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; TRAVEL / Special Interest / Literary; TRAVEL / Essays & Travelogues; Lake of the Woods -- Description and travel; Lake of the Woods Region -- Description and travel; Lake of the Woods Region -- Social life and customs